Toxoplasmosis in females from Al-Anbar, Iraq - Salaah Aldeen M. Sadeq Alkubaisi; Ibrahim Abdul-Hussein Swear Al-Zubaidy (مجلة كلية الطب, 2023)
Background: Toxoplasmosis is a common zoonotic disease affecting one-third of the world population with potentially serious health implications.